RESEARCHING NARRATIVELY WITH BODIES STORIES IN PHYSICAL EDUCATION - María Esther Prados Megías; José Ignacio Rivas Flores (Universidad Nacional del Nordeste, 2019)
The body and everything that it means in human relationships is fashionable. However, today's society continues to present us the corporeal as a mechanized, commodified and reified issue. The different media discourses and the hegemonic corporal models, both in cultural and educational spaces, are filtered in our sensoriality as models to be reproduced. Hence, to access to the experience of people through their accounts, their stories and body biographies, provide us with a way to understand and understand how people live their bodies through movement. The focus and positioning of the narrative inquiry can give us clues to incorporate and consider that researching, especially in the field of the body in education, implies a social, political and ethical commitment that is not alien to people, especially because it concerns the most intimate, the body, that boundary between the private and the public, between the expressed and the "lived-sense". Through stories we access the imaginary that the students build about the idea of being educators of the movement, since in their stories practical schemes for decision making are shown, both in their formation and in their future profession. The stories and performances of the students allow us to glimpse elements that let us to make the body a space of discursive convergence in what we have called "dietary bodies, suffered bodies, imagined bodies and languaged bodies".